PENGARUH EMPLOYEE COMMUNICATION TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR YANG DIMEDIASI OLEH EMPLOYEE ENGAGEMENT PADA KARYAWAN DI BEBERAPA FAKULTAS UNIVERSITAS TRISAKTI JAKARTA - Agustiani Rifania Amanda (Jurnal Manajemen dan Pemasaran Jasa, 2014)
This research is about “The Effect of Emoloyee Communication On Organizational Citizenship Behavior Mediated by Emmployee Engagement Employees On Faculty of Economics, Faculty of Dentistry, and Faculty of Art and Design Trisakti University Jakarta”. The background of this study is to analyze the factors that can influence the Organizational Citizenship Behavior OfEmployees Faculty of Economics, Faculty of Dentistry, and Faculty of Art and Design Trisakti University Jakarta. Several factors can affect the Organizational Citizenship Behaviorincluding Employee communication and Employee engagement. The purpose of this study was to examine the effect of the Employee Communication to Organizational Citizenship Behavior through Employee Engagement. The design of this research using primary data obtained by distributing questionnaires to 200 Employees Faculty of Economics, Faculty of Dentistry, and Faculty of Art and Design Trisakti University Jakarta. Data analysis method used in this researchis Structural Equation Model (SEM).The results of this research concluded that there is a positive influence on the Employee Communication against Organizational Citizenship Behavior, there is a positive influence on Employee Communication against Employee Engagement, and there is a positive influence on Employee Engagement against Organizational Citizenship Behavior.Keywords : Employee Communication, Employee Engagement, Organizational Citizenship Behavior